SENAM IRAMA DALAM MENGEMBANGKAN KECERDASAN KINESTETIK ANAK USIA 5-6 TAHUN DI TK KARYA YOSEF - Kadi, Kadi; Halida, Halida; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the rhythmic gymnastics in developing kinesthetic intelligence in children aged 5-6 years in the Catholic Private Kindergarten Works Yosef Pontianak. This research is done by qualitative approach and descriptive. The data sources are the B2 class teachers and the B2 group of 38 students. Research instruments: interview guide, observation guide, and documentation data. It is generally collected that the teacher has been able to define kinesthetic intelligence specifically so that the rhythmic gymnastics performed every Friday is to develop the optimal kinesthetic intelligence of the child. In particular; (1) Understanding the teacher is already know the definition of kinesthetic intelligence, kinesthetic intelligence characteristics, defini- tion of gymnastics rhythm and elements of gymnastics can exemplify and practice in the field; (2) Implementation of rhythmic gymnastics that teachers have made several movements in rhythmic gymnastics to develop six aspects of kinesthetic intelligence such as coordination, balance, strength, flexibility, endurance, speed; (3) The ability of children in exercising gymnastes that children are able to perform gymnastics rhythm from the movement of heating, core and cooling movement. And can make footsteps in rhythmic gymnastics. Keyword :Rhythmic Gymnastics, Kinesthetic Intelligence.